The Effect of Rosemary Extract on the Sensory Quality of Flaxseed Oil During Storage - Sielicka, Maria; Małecka, Maria (Studia Oeconomica Posnaniensia, 2017)
The aim of the study was to evaluate the effect of rosemary extract on the sensory quality of flaxseed oil during storage in practical storage conditions (at room and refrigerator temperature). The flaxseed oil with 0.05% rosemary extract, 0.02% BHT and control sample were subjected to a regular sensory analysis. The intensity of bitter taste, nutty, oxidized and grassy flavours was evaluated with the use of a quantitative descriptive analysis (QDA) by a trained sensory panel. The addition of rosemary extract and BHT in the amount of 0.05% and 0.02%, respectively, to the fresh flaxseed oil did not cause a statistically significant change in its taste perception. Storage in practical conditions revealed beneficial effects of these substances on the sensory quality of the oil as compared to the control samples. The addition of rosemary extract periodically lowered the intensity of a bitter taste. The addition of BHT delayed the appearance of an unacceptable level of bitterness, and thus extended the shelf-life of flaxseed oil by 14 days at room temperature and 28 days under refrigerator storage.